Spontaneous Delayed Migration/Shortening of the Pipeline Embolization Device: Report of 5 Cases - Chalouhi, N.; Tjoumakaris, S.I.; Gonzalez, L.F.; Hasan, D.; Pema, P.J.; Gould, G.; Rosenwasser, R.H.; Jabbour, P.M. (American Journal of Neuroradiology, 2013)
SUMMARY: Five patients were found to have spontaneous delayed migration/shortening of their Pipeline Embolization Devices on follow-up angiography. The device migrated proximally in 4 patients and distally in 1 patient. One patient had a subarachnoid hemorrhage and died as a result of migration of the Pipeline Embolization Device, and another patient presented with complete MCA occlusion and was left severely disabled. Mismatch in arterial diameter between inflow and outflow vessels was a constant finding. Migration of the Pipeline Embolization Device was managed conservatively, with additional placement of the device, or with parent vessel occlusion. Obtaining complete expansion of the embolization device by using a longer device, increasing vessel coverage, using adjunctive aneurysm coiling, and avoiding dragging and stretching of the device are important preventive measures. Neurointerventionalists should be aware of this potentially fatal complication and take all necessary preventive measures. PEDPipeline Embolization DeviceSHAsuperior hypophyseal artery